Strategi Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Kecerdasan Intrapersonal Dalam Meningkatkan Nilai Karakter Diri Siswa di Madrasah Ibtidaiyah Mambaul Huda Al-Islamiyah Ngabar Ponorogo - Muhammad Asfani Ilham Putra Laili; M. Asvin Abdurrahman; Asaduddin Luqman (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study aims to describe the learning strategies of Islamic Religious Education (PAI) at MI Mambaul Huda Al-Islamiyah Ngabar Ponorogo, to explain the implementation of PAI learning strategies based on intrapersonal intelligence, and to analyze how these strategies contribute to the improvement of students’ personal character values. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, involving the vice principal for curriculum, PAI teachers, and students as research subjects. The findings reveal that PAI learning strategies at MI Mambaul Huda Al-Islamiyah are designed in a varied manner, tailored to students’ characteristics and potential. Teachers integrate affective, psychomotor, and intrapersonal approaches in the learning process. The strategies include interactive lectures, group discussions, hands-on practice, self-reflection, and individual projects such as writing personal experiences and creating calligraphy artworks. Teachers also provide personal guidance to help students understand themselves more deeply. This approach is supported by a conducive school environment, although challenges such as limited time and diverse student characteristics remain. The intrapersonal intelligence-based learning strategies significantly contribute to the enhancement of students’ personal character values. Through self-awareness and self-understanding, students develop empathy, responsibility, and social care. These values are instilled not only through classroom materials but also through habitual and exemplary activities such as regular charity (infak), community service, and public speaking programs (muhadharah). Thus, PAI learning in this madrasah not only focuses on cognitive aspects but also holistically shapes students’ religious and social character.